Threading Memoryscapes: mental mapping and cultural storytelling through string, space & place - Mat Nayan, Nadiyanti; Ahmad, Suriati; Hassan, Norasikin; Syed Guntur, Noralya Balqis; Suhazeli, Arsyad Jazli (2025)
This teaching innovation transforms the exploration and understanding of cultural landscapes by creatively integrating mental mapping, tactile storytelling, and place-based learning. Conducted with landscape architecture students in various heritage towns and kampongs in Perak, the project blends cognitive mapping with physical expression using maps, archival images, and string to create interactive "memoryscapes". Students are challenged to translate their personal perceptions, local narratives, and community memories into spatial forms, resulting in layered installations that visualise both the physical and mental geographies of a place. They externalise internalised knowledge by threading strings between locations, stories, and symbolic references, effectively making the invisible visible. This approach encourages critical reflection on how cultural identity, memory, and space are mentally and emotionally mapped. Offering a multisensory learning experience that combines fieldwork, ethnographic inquiry, and visual communication, this methodology allows students to cocreate meaning in collaboration with the local context. Mental mapping serves as both a process and a product, fostering empathy, cultural sensitivity, and spatial awareness. The use of analogue tools and embodied practices deepens engagement and bridges theory with experience, while promoting creativity, collaboration, and critical thinking. This method redefines mapping as an act of cultural storytelling, where students document not only what is seen but also what is felt, remembered, and imagined. It presents a scalable, low-tech, high-impact model for teaching cultural landscapes in an immersive, reflective, and deeply human-centred way.